PROVISION OF STIMULANTS MADE OF PEG 6000 AND OLEOCHEMICALS IN INCREASING THE PRODUCTION OF RUBBER PLANTATIONS - Rahayu, Murni Sari; Syamfitri, Syamfitri; Dharma, Surya; Pebrian, Darius El (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Indonesia’s rubber plants nationally is still relatively low compared to other natural rubber-producing countries, which is 858 kg/ha/year. The lack of precision of the inefficient exploitation and tapping system implemented by rubber farmers, both community plantations, government and private, is one of the causes of low rubber production in Indonesia. This study aims to determine the influence of the production and physiology of latex in the PB 260 clone community rubber plant after being given a stimulant made of PEG 6000 and oleochemicals. The research was carried out in a community rubber plantation, located in Galang District, Deli Serdang Regency, North Sumatra Province. The altitude of the place is 25 m above sea level with the Ultisol soil type. The research began in July 2022 to November 2022. The plant material used in the field is a 20-year-old PB260 clone rubber plant. Research observations include plant production in the field on smallholder rubber plantations, as well as latex physiological analysis conducted at the Laboratory of the Faculty of Agriculture, Islamic University of North Sumatra and the Sungei Putih Research Institute, Field experiments used a three-replicate factorial group random design with PEG 6000 and Oleochemistry as treatments. The A1 treatment generally had the best effect on all the observational parameters of the study. The combination of PEG 6000 3% and Oleochemistry had an insignificant effect on latex production, rubber dryness, rubber physiology, and rubber histology. However, statistically the combination of P1A1 has a positive effect on rubber plants.